(untitled) (Humanis, 2026)
This research entitled "English Register in Social Media Instagram". This research is conducted with the aim at identifying and mapping the use of English registers in social media Instagram and specifically is to find out the function of the usage of those registers. This research is a-qualitative descriptive research. The method applied for this research is observation method with note-taking and screen shot technique. This research applied register theory from Halliday (1994).